2018
DOI: 10.11002/kjfp.2018.25.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying and harvest time on the physicochemical properties of the most common Korean persimmon leaves

Abstract: long been associated with the prevention of diseases such as scurvy. Ascorbic acid is easily degraded, however, as a result of several factors such as temperature, pH, light intensity, oxygen, enzymes, metallic catalyzers, relative humidity, physical damage, frost damage, adverse handling, and storage conditions (3,4). Moreover, it is important to recognize the seasonal changes in the mineral contents of the leaves and identify the optimum harvesting time. Leaf-nutrient analysis plays an important role in eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…PL are commonly used in a dried form to make functional tea. The moisture content of fresh persimmon is around 75–80%, while the powder obtained from dried leaves contains 10 and 4% moisture when dried using hot-air and freeze-drying, respectively [ 1 ]. The major pigments in PL are chlorophylls, xanthophylls, anthocyanins, and carotenes, which are responsible for changing colors throughout the growing season.…”
Section: Proximate Composition Of Plmentioning
confidence: 99%
See 4 more Smart Citations
“…PL are commonly used in a dried form to make functional tea. The moisture content of fresh persimmon is around 75–80%, while the powder obtained from dried leaves contains 10 and 4% moisture when dried using hot-air and freeze-drying, respectively [ 1 ]. The major pigments in PL are chlorophylls, xanthophylls, anthocyanins, and carotenes, which are responsible for changing colors throughout the growing season.…”
Section: Proximate Composition Of Plmentioning
confidence: 99%
“…The major pigments in PL are chlorophylls, xanthophylls, anthocyanins, and carotenes, which are responsible for changing colors throughout the growing season. Hossain et al [ 1 ] investigated the Hunter color values of the most common PL grown in Korea and found that L* (lightness), a* (yellowness), and b* (redness) values were 57.92–62.14, 1.42–2.31, and 15.96–20.13, respectively, for the freeze-dried leaves. In contrast, Chung et al [ 19 ] found that the L*, a*, and b* values were 43.55, −15.05, and 26.83, respectively, for fresh PL.…”
Section: Proximate Composition Of Plmentioning
confidence: 99%
See 3 more Smart Citations